2010
DOI: 10.1111/j.1439-037x.2010.00449.x
|View full text |Cite
|
Sign up to set email alerts
|

Drought Effect on Grain Number and Grain Weight at Spike and Spikelet Level in Six-Row Spring Barley

Abstract: Water is the primary regulator of yield formation in cereals. The effect of water limitation and its timing on development of yield components were studied in detail at spike and spikelet level in spring barley (Hordeum vulgare L.). An experiment with three watering treatments (control watering, CONT; drought prior to pollination, DR1 and terminal drought, DR2) was set up in a large greenhouse (20 × 30 m). In addition to watering treatments, two NPK fertilizer application rates (0 and 120 kg N ha−1) were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
48
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 51 publications
10
48
1
Order By: Relevance
“…Indeed, the current study confirmed this by the presence of variation amongst the studied 11 barley genotypes. The effects of water stress on the yield reduction of barley have been well documented [28,29].The present study showed that yield and yield components were significantly reduced in all tested genotypes due to water deficit during tillering and stem elongation stages (e.g., yield reduced by 66% and 54% at SS and SE, respectively; Table 4). These results indicated that drought stress during the pre-anthesis period reduced grain yield by decreasing the number of fertile spikes and grains per plant (Table 4).…”
Section: Resultssupporting
confidence: 71%
“…Indeed, the current study confirmed this by the presence of variation amongst the studied 11 barley genotypes. The effects of water stress on the yield reduction of barley have been well documented [28,29].The present study showed that yield and yield components were significantly reduced in all tested genotypes due to water deficit during tillering and stem elongation stages (e.g., yield reduced by 66% and 54% at SS and SE, respectively; Table 4). These results indicated that drought stress during the pre-anthesis period reduced grain yield by decreasing the number of fertile spikes and grains per plant (Table 4).…”
Section: Resultssupporting
confidence: 71%
“…Toth et al (2005) attributed the reduction in photosynthetic pigments to abrupt damage of the PSII units, loss of their capacity of oxygen evolution leading to a restricted electron transport and thus reduced rate of photosynthesis. The reduced rate in photosynthesis may have contributed to the reduction in plant height, number of tiller, fresh weight and dry weight since the production of biomass is the result of photosynthesis (Rajala et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…At that stage, the limited availability of water and assimilates affects the translocation processes, from sources to sinks, filling grains. In oat, however, water deficit at post-anthesis mainly decreased the number of grains (Peltonen-Sainio & Mäkelä, 1995), similarly to wheat (Rajala et al, 2011), probably due to limited source capacity. Fábián et al (2011) showed that water deficit occurring after pollination, during early grain development stage, decreases the embryo size and increases the degradation of cell layers surrounding the ovule.…”
Section: Late Season Drought and Irrigationmentioning
confidence: 96%
“…For spring cereals, long coleoptiles and vigorous seedling emergence are important traits in Boreal conditions, where there is uneven precipitation and a short growing season (reviewed in Mäkelä et al, 2008). In spring barley (Hordeum vulgare L.), early season water deficit reduced both the sink and source capacity of plants through decrease in photosynthesis and thereby dry weight accumulation and number of grains (Rajala et al, 2011). According to Jamieson et al (1995), a water deficit related decrease in dry weight accumulation of barley during the early phases of growth is mainly due to reduced radiation use efficiency, which does not recover completely after stress relief.…”
Section: Early Season Drought and Irrigationmentioning
confidence: 99%
See 1 more Smart Citation